The development of assessment scales of physical training of wrestlers at the stage of basic specialized training - Latyshev, S. V. (Physical Education of Students, 2013)
The aim of research is to select tests and develop scales for identification of premises of wrestlers preferrances of definite wrestling style. The participants of the research were 92 wrestlers of free style aged 16-17 years at the stage of specialized basic training from Donetsk, Lviv, Ternopyl, Ivano-Frankyvsk and Khmelnitsk regions. A set of 15 tests is developed. Five new tests developed by the author with the account of new trends in wrestlers training were included. Average group indexes of physical conditions for 16-17 aged wrestlers as well as Ketle index were identified. Five point scales for identifying Ketle index and physical conditions of wrestlers aged 16-17 years were stated. They enable to highlight preconditions of wrestlers to choose a definite wrestling style.